Angulations of Anterior Teeth With Reference to the Alveolar Bone Measured by CBCT in a Chinese Population. Issue 4 (August 2015) - Zhang, Shanchuan; Shi, Xiaowei; Liu, Hongchen
Abstract : Objective: To analyze angulations of anterior teeth with reference to the alveolar bone. Methods: Cone-beam computed tomographic (CBCT) images of 105 participants were taken with the same machine (ProMax 3D Max CBCT), showing the intact anterior teeth. The angulations formed between the long axis of the anterior teeth and the alveolus were measured using cross-sectional images. The thicknesses of alveolar bone on different area of root surfaces were also measured. Results: Maxillary anterior teeth were found to be close to the buccal alveolar surface in apical level with the angulations referred to alveolar bone in center incisor, lateral incisor, and canine were 17.65 ± 6.8, 18.79 ± 7.4, and 23.82 ± 6.96 degrees, respectively. Means of angulations of mandibular anterior teeth were less than 8 degree. The thicknesses of buccal bone at mid-root level in 77% to 90% maxillary anterior teeth were less than 1 mm. The determinations provided high intrarater/interrater reliability. Conclusions: The application of CBCT is reliable for a complete calculation of angulations and thicknesses in a Chinese Han population. As a result, adequate planning combined with image examination preoperatively would contribute to a favorable outcome.